2017
DOI: 10.17576/jkukm-2017-29(1)-07
|View full text |Cite
|
Sign up to set email alerts
|

Two Component Injection Moulding of Bi-material of Stainless Steel and Yttria Stabilized Zirconia – Green Part

Abstract: The two component injection molding (2C-PIM) is a promising technique for production of small, complex and high density, metal-ceramic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…While in spot 2 area, elements of Ca and P were higher than Fe which is represent HA. Sintering temperature influences the mechanical properties of the final part in terms of its density, hardness, flexural strength and Young’s modulus [ 11 ]. Sintering was conducted on the 61 vol% brown part at different temperatures such as 1000°C, 1100°C, 1200°C and 1300°C, for 1 hour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While in spot 2 area, elements of Ca and P were higher than Fe which is represent HA. Sintering temperature influences the mechanical properties of the final part in terms of its density, hardness, flexural strength and Young’s modulus [ 11 ]. Sintering was conducted on the 61 vol% brown part at different temperatures such as 1000°C, 1100°C, 1200°C and 1300°C, for 1 hour.…”
Section: Resultsmentioning
confidence: 99%
“…Thian et al . [ 11 ] found that the sintering time will not affect the sintered part, however, the sintering temperature will influence the physical and mechanical properties of the sintered part. Cihlar and Trunec [ 60 ] had conducted a study on HA using PIM and discovered that sintering time indeed did not give any effects on the HA phase after 1–4 hours of sintering.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 17-4PH stainless steel and 3 mol% yttria-stabilized zirconia are renowned materials in engineering. While 17-4PH is associated with excellent corrosion resistance and mechanical strength, zirconia is well-known for its fracture toughness, flexural strength, excellent wear resistance, good biocompatibility, and high-temperature stability [ 18 , 19 , 20 ]. The 2C-µPIM-processed bi-material micro-sized components of 17-4PH and zirconia can be used in many engineering applications, such as medical implants, automobile engines, and gas turbines, where metal–ceramic combinations are often used to achieve diverse functionalities at lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous research, additional process such as secondary process will spend more cost compared to by using 2C-PIM process [3]. The secondary process is referred to produce interlayer or any combination of two materials.…”
Section: Introductionmentioning
confidence: 99%